China and the Future of AI - Shafiullah Farzayee (Department of Political Science - Universitas Sains Al-Qur’an, 2020)
The progress of technology is currently remarkable and very fast, especially Artificial Intelligent or AI. China, as the largest emerging and biggest developing country, has significant AI growth. It is near that China will probably become the pioneer in the fifth generation of technologies, making the US worry. Along with its remarkable economic growth, China makes research and development agenda as the top priority. In this regard, this paper seeks to explain China and the future of AI, including its current progress.